Comparison of concentric movement velocity with push band 2.0 and Vicon motion capture during resistance exercises - Pelka, E. Z.; Williams, A.; McLaughlin, D.; Gadola, C.; Slattery, E.; Claytor, R. (ISBS Proceedings Archive (Michigan), 2020)
We compared concentric movement velocity (CMV) measured with PUSH Bands (v.2.0) and a Vicon motion capture system (MC) during back squat (SQ) and bench press (BP) resistance exercises (RE) completed using a 2-dimensional smith machine. Twelve experienced resistance-trained males completed 10 repetitions at 50% of 1-repetiton maximum (1RM), and 6 repetitions at 75% 1RM for both BP and SQ. Use of Least-squares means contrasts suggests CMV measures did not differ between measurement technologies. Also, there is no indication of systematic bias between PUSH and MC. PUSH provides an accurate and reliable measurement of CMV during moderate and high intensity SQ and BP as compared with MC.